Stereotaxic biopsy of brainstem tumors in pediatrics. Current indications and future perspectives - del Rio, Ramiro José; Gonzalez Ramos, Javier (Revista Argentina de Neurocirugía, 2020)
Introduction: Brainstem tumors are frequent neoplasms in pediatrics. During the last decades and with the advancement of imaging methods, classifications with diagnostic and therapeutic implications were developed. Today the stereotaxic biopsy is a controversial topic especially in diffuse lesions. Objectives: To update the indications for this type of procedure in pediatrics, also analyzing future perspectives. Discussion: At the present, stereotaxic biopsies in brainstem tumors have precise indications for tumors without surgical indication or in non-surgical cases. In patients with atypical lesions defined by MRI, clinical presentation or age outside the usual range, diagnosis by pathological anatomy becomes necessary. Advances in molecular biology in oncology have sparked interest in diffuse gliomas of the pons. Nowadays, the performance of this surgery is accepted in the case of research protocols, although it has no relevance in the patient`s outcome. Taking tissue to determine the application of target treatments together with techniques that allow the application of drugs by microcatheters placed directly in the lesion are possible future applications of stereotaxy for this type of tumors. Conclusions: Brainstem tumors in pediatrics, as they are a frequent pathology, require a special chapter. Advances in the classification of these, together with new molecular biology study methods make it necessary to define the indications for stereotaxic biopsy for this type of lesion, which may change the paradigm in the future.